Discriminant factors of flood insurance demand for flood-hit residential properties: A case for Malaysia - Aliagha, Godwin Uche (Blackwell Publishing Inc., 2015)
Securing flood insurance for real estate properties in flood-hit areas is rather uncertain under the Malaysian scenario. This study attempts to identify the demand-side factors of flood insurance in coastal residential areas, and to examine how these factors differentiate between two groups of respondents, namely flood insurance purchasers and non-purchasers, using discriminant analysis. Tests using Wilks' lambda, eigenvalues, canonical correlation, functions at group centroids, and classification accuracy have provided strong evidence of significant differences between the two groups based on physical exposure/susceptibility to flood, resilience/adaptive capacity to flood, and overall perception of vulnerability. The most important variables accounting for group differences were low-elevation house site, flood depth entering house, perception about high-priced flood insurance, and level of income. The likelihood of purchasing flood insurance increased with higher physical exposure/susceptibility and overall perception of vulnerability. Resilience/adaptive capacity to flood event also increased with higher levels of income and education.